SAT0361 Chest computed tomography as an alternative to high resolution manometry for the diagnosis of scleroderma esophagus. (15th June 2017) - Panopoulos, S; Bournia, VK; Karamanolis, G; Denaxas, K; Zorbala, A; Sfikakis, PP
Abstract : Background: Severe esophageal disease in patients with systemic sclerosis (SSc), referred as scleroderma esophagus, is characterized by ineffective or absent peristalsis along with hypotensive esophagogastric junction (hEGJ). The associations between scleroderma esophagus and different clinical and laboratory manifestations of SSc are still controversial. Objectives: To assess associations between scleroderma esophagus, diagnosed by high resolution manometry (HRM), and other manifestations of disease. Methods: Fifty-four consecutive SSc patients (49 women, mean age 50.6±11.6 years) with esophageal symptoms underwent clinical interview, medical records review and HRM. HRMs were analyzed according to the Chicago Classification in order to provide esophageal motility diagnosis; EGJ <9 mmHg was considered hypotensive. Demographic characteristics, patient-reported symptoms, SSc subtypes, pulmonary fibrosis, cutaneous ulcers, and anti-Scl-70 positivity were compared between SSc patients with or without scleroderma esophagus. Comparison was also performed in chest computed tomography (CT) findings of esophageal lumen in 26 patients with available data. Esophageal dilatation was deemed present when the diameter was >9 mm. Results: Absent contractility was present in 37 (68.5%) patients; among these patients hEGJP was found in 32, thus 32/54 (59.2%) patients had classic scleroderma esophagus. There were no associations with gender, age, esophageal symptoms, skin involvement extent, anti-Scl-70, pulmonary fibrosis and cutaneous ulcers. Notably, esophageal dilation on chest CT was more frequent in patients with scleroderma esophagus compared to those without (77% vs. 8%, p=0.04, respectively). Conclusions: Scleroderma esophagus diagnosed by HRM was present in less than 2/3 of symptomatic patients with SSc and associated only with esophageal dilation (>9mm) in CT. Although further studies are needed, esophageal dilation on chest CT may be a non-invasive alternative for evaluation of SSc patients with esophageal symptoms. Disclosure of Interest: None declared